Prognostic impact of dissected lymph node count on patients with node-negative gastric cancer - Huang, Chang-Ming (The WJG Press, 2009)
AIM: To investigate the long-term effect of the number of resected lymph nodes (LNs) on the prognosis of patients with node-negative gastric cancer. METHODS: Clinical data of 211 patients with gastric cancer, without nodal involvement, were analyzed retrospectively after D2 radical operation. We analyzed the relationship between the number of resected LNs with the 5-year survival, the recurrence rate and the post-operative complication rate. RESULTS: The 5-year survival of the entire cohort was 82.2%. The total number of dissected LNs was one of the independent prognostic factors. Among patients with comparable depth of invasion, the larger the number of resected LNs, the better the survival (P < 0.05). A cut-point analysis provided the possibility to detect a significant survival difference among subgroups. Patients had a better long-term survival outcomes with LN counts ≥ 15 for pT1-2, ≥ 20 for pT3-4, and ≥ 15 for the entire cohort. The overall recurrence rate was 29.4% within 5 years after surgery. There was a statistically significant, negative correlation between the number of resected LNs and the recurrence rate (P < 0.01). The post-operative complication rate was 10.9% and was not significantly correlated with the number of dissected LNs (P > 0.05). CONCLUSION: For node-negative gastric cancer, sufficient number of dissected LNs is recommended during D2 lymphadenectomy, to improve the long-term survival and reduce the recurrence. Suitable increments of the dissected LN count would not increase the post-operative complication rate.